Anti-inflammatory, antioxidant, and other health effects of dragon fruit and potential delivery systems for its bioactive compounds - BORGES, Ana Cláudia Abdalla; NISHIKITO, Daniele Franceschi (130, 2023)
Dragon fruit (Hylocereus genus) has the potential for the prevention of diseases associated with inflammatory and oxidative processes. We aimed to comprehensively review dragon fruit health effects, economic importance, and possible use in delivery systems. Pubmed, Embase, and Google Scholar were searched, and PRISMA (Preferred Reporting Items for a Systematic Review and Meta‐Analysis) guidelines were followed. Studies have shown that pitaya can exert several benefits in conditions such as diabetes, dyslipidemia, metabolic syndrome, cardiovascular diseases, and cancer due to the presence of bioactive compounds that may include vitamins, potassium, betacyanin, p‐coumaric acid, vanillic acid, and gallic acid. Moreover, pitaya has the potential to be used in food and nutraceutical products as functional ingredients, natural colorants, ecologically correct and active packaging, edible films, preparation of photoprotective products, and additives. Besides the importance of dragon fruit as a source of bioactive compounds, the bioavailability is low. The development of delivery systems such as gold nanoparticles with these compounds can be an alternative to reach target tissues.

A pitaia (gênero Hylocereus) tem potencial para a prevenção de doenças associadas com processos inflamatórios e oxidativos. Nosso objetivo foi revisar exaustivamente a fruta do dragão efeitos na saúde, importância econômica e possível uso em sistemas de entrega. Pubmed, Embase e Google Scholar foram pesquisados, e PRISMA (Preferred Reporting Items for a Systematic Review e meta-análise) foram seguidas. Estudos têm mostrado que a pitaya pode exercer diversas benefícios em condições como diabetes, dislipidemia, síndrome metabólica, doenças cardiovasculares, e câncer devido à presença de compostos bioativos que podem incluir vitaminas, potássio, betacianina, ácido p-cumárico, ácido vanílico e ácido gálico. Além disso, a pitaya tem potencial para ser utilizados em alimentos e produtos nutracêuticos como ingredientes funcionais, corantes naturais, embalagens corretas e ativas, filmes comestíveis, preparação de produtos fotoprotetores e aditivos. Além da importância da pitaia como fonte de compostos bioativos, a biodisponibilidade é baixo. O desenvolvimento de sistemas de entrega como nanopartículas de ouro com esses compostos pode ser uma alternativa para atingir os tecidos-alvo.
Efeitos anti-inflamatórios, antioxidantes e outros efeitos na saúde da pitaia e potenciais sistemas de entrega para seus compostos bioativos
Artigo científico válido como TCC. Publicado em: Pharmaceutics 2023, 15, 159. https://doi.org/10.3390/pharmaceutics15010159
Keywords: Alimentos funcionais; Compostos bioativos; Saúde; Prevenção de doenças; Produção Alimentícia